EVOLUŢIA POLITICILOR ÎN SISTEMUL NAŢIONAL AL BIBLIOTECILOR DIN REPUBLICA MOLDOVA - HARJEVSCHI, Mariana (BIBLIOPOLIS, 2020)
Policy Development within the National Libraries' System in Moldova aims to reveal the problems related to establishing, developing and harmonization of state policy in the field of libraries as a factor of modernization of libraries. Scientific novelty of the results lies in conceptualizing specific library policy; description of policy developments from legal and librarianship prospective during 1991-2013.